The Use of Learning Management Systems (LMS) to Enhance the Effectiveness of English Language Teaching in MT's Ihya Assunnah Kolaka - Ahmad Dani; Sam Hermansyah; Maulina; Syarif Amin; Andi Rachmawati Syarif (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
The rapid advancement of digital technology has transformed English language teaching, particularly through the adoption of Learning Management Systems (LMS) such as Google Classroom or Moodle. This study aimed to investigate the effectiveness of LMS in enhancing the overall quality and outcomes of English language teaching at MTs Ihya Assunnah Kolaka, Southeast Sulawesi, Indonesia. Employing a quasi-experimental pretest-posttest control group design, the research involved 23 eighth-grade students. The experimental group received English instruction integrated with LMS features for interactive materials, assignments, discussions, and feedback, while the control group followed conventional face-to-face teaching methods. Data were collected through pre- and post-tests focusing on English language skills (listening, speaking, reading, and writing) and analyzed using paired and independent sample t-tests. The findings revealed a statistically significant improvement in the experimental group’s English proficiency compared to the control group (p < 0.05), with notable gains in student engagement, motivation, and autonomous learning. Students also reported positive perceptions toward the flexibility and interactivity provided by the LMS. This study demonstrates that LMS can effectively support English language teaching in madrasah settings with limited resources. The integration of LMS is recommended to promote more student-centered and interactive learning experiences aligned with the Kurikulum Merdeka.